Pengaruh Penggunaan Strategi Pembelajaran Aktif Tipe Giving Question and Getting Answer Terhadap Hasil Belajar Matematika Siswa Sekolah Dasar - Ine Febriyanti; Arjudin Arjudin; Abdul Kadir Jaelani (Griya Journal of Mathematics Education and Application, 2022)
This study aims at determining the effect of the use of an active learning strategy type of giving questions and getting answers on the mathematics learning outcomes of elementary students. This research is under Non-equivalent Control Group Design of Quasi Experimental Design where purposive sampling is used as sampling technique. The population of this study consists of 44 students with observation, tests, and documentation used as the data collection technique. The research instrument used are test of learning outcomes and observation sheets. The normality test was done by calculating the data in the form of pre-test and post-test mathematics learning outcomes using the Kolmogorov Smirnov formula with a sig level of 5% (0.05), after the data was normally distributed, the homogeneity test obtained from the post-test calculations, then hypothesis testing with t-test using the calculation of students’ post-test data. The results of data analysis shows that the value of sig 2 tailed is 0.000, which is less than 0.05, thus, based on the research hypothesis, if the value of sig 2 tailed ≤ 0.05 t-table, then Ho is rejected and Hₐ is accepted. This shows that there is an effect of using an active learning strategy with the type of giving questions and getting answers on the mathematics learning outcomes of elementary students. The results of this research are expected to be used as a reference for further research on different subjects.